STRATEGI MENINGKATKAN PARTISIPASI AKTIF PEREMPUAN DALAM PERENCANAAN PEMBANGUNAN DI NEGERI KEDAH, MALAYSIA - Maulidiah, Sri; Muslim, Sakinah; Rauf, Rahyunir; Yuslaini, Nina; Hayati, Restu; Rahyunir, Muhammad Hafizh (Universitas Padjadjaran, 2024)
In development planning, women's involvement is imperative in order to create conditions which puts women in a fair position, without discrimination. This condition does not only occur in Indonesia but also occurs in developing countries such as Malaysia. From this phenomenon, the Community Service Team (PKM) of Universitas Islam Riau (UIR) in collaboration with Universiti Utara Malaysia (UUM) located in the Government of Yan District Negeri Kedah, Malaysia made an activity program with the theme of being an active woman in development planning. The purpose of PKM activities (1) is to provide an understanding of the importance of women's participation in development planning in Kedah, Malaysia, (2) to provide an understanding of the direct impact that will be felt by the government if women can play an active role directly in development planning. The method used uses the Rapid Rural Appraisal (RRA), Participatory Rural Appraisal (PRA), Actian Research (AR) methods. The results of PKM activities show (1) an increase in the interest and enthusiasm of counseling participants in the involvement of governance in Kedah, Malaysia. (2) an increase in the understanding of counseling participants on the importance of women's participation in development planning in Kedah, Malaysia. (3) there is an increase in the understanding of counseling participants about the direct impact that will be felt by the Kedah State government if women can play an active role directly in the development planning of Kedah State, Malaysia. (4) there is an increase in maximizing programs in the field of development and in the field of community empowerment that are directly related to meeting the needs of women and children of Kedah State, Malaysia.Dalam perencanaan pembangunan, keterlibatan perempuan menjadi keharusan yang tujuannya agar tercipta kondisi yang menempatkan perempuan dalam posisi yang adil, tanpa diskriminasi. Kondisi seperti ini tidak hanya terjadi di Indonesia, tetapi juga terjadi pada negara-negara berkembang seperti Malaysia. Dari fenomena tersebut, Tim Pengabdian Kepada Masyarakat (PKM) Universitas Islam Riau (UIR) bekerjasama dengan Universiti Utara Malaysia (UUM) bertempat di Pemerintah Yan District,Negeri Kedah, Malaysia membuat program kegiatan dengan tema menjadi perempuan aktif dalam perencanaan pembangunan. Tujuan kegiatan PKM (1) untuk memberikan pemahaman tentang pentingnya partisipasi perempuan dalam perencanaan pembangunan di Negeri Kedah, Malaysia, (2) untuk memberikan pemahaman tentang dampak langsung yang akan dirasakan oleh pemerintah jika perempuan dapat berperan aktif secara langsung dalam perencanaan pembangunan. Metode yang digunakan menggunakan metode Rapid Rural Appraisal (RRA), Participatory Rural Appraisal (PRA), dan Action Research (AR). Hasil kegiatan PKM menunjukkan (1) adanya peningkatan animo dan antusiasme peserta penyuluhan dalam keterlibatan penyelenggaraan pemerintahan di Negeri Kedah, Malaysia. (2) Adanya peningkatan pemahaman peserta penyuluhan tentang pentingnya partisipasi perempuan dalam perencanaan pembangunan di Negeri Kedah, Malaysia. (3) Adanya peningkatan pemahaman peserta penyuluhan tentang dampak langsung yang akan dirasakan oleh pemerintah Negeri Kedah jika perempuan dapat berperan aktif secara langsung dalam perencanaan pembangunan Negeri Kedah, Malaysia. (4) Adanya peningkatan memaksimalkan program di bidang pembangunan dan di bidang pemberdayaan masyarakat yang berhubungan langsung dengan pemenuhan kebutuhan perempuan dan anak-anak Negeri Kedah, Malaysia.